Development of a portable electronic device for the detection and indication of fireworks and firecrackers for security personnel - Aaron Don Munsayac Africa; Stephanie Claire Alberto; Travis Evan Tan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The use of fireworks and firecrackers to celebrate festivities is a very common activity in the Philippines. But due to the lack of strict control and regulation, there are unwanted risks of accidents from occurring due to the poor handling and storage conditions of these devices. Proper monitoring is important to reduce any unnecessary risks imposed on human life and property. While existing storage monitoring devices exist, the developed prototype is designed to contain sensors that are more suited in monitoring the ideal conditions of where the fireworks are stored. Monitoring the climate conditions on these devices may seem trivial at first, but such climate change can involve a rapid rise in temperature that can accidentally ignite the fireworks and deal with catastrophic damage. Another concern is the rise of humidity that may alter that chemical characteristics of the gunpowder stored in the fireworks.  Such changes may not have any noticeable effects until it arrives in the consumer, that may experience an unwanted and unintended change in the performance of the fireworks leading to accidents. Therefore, it is important for this device to properly monitor the surrounding area then indicate various forms of alarms as a method of redundancy.